Impact analysis studies of clinical prediction rules relevant to primary care: a systematic review. Issue 3 (15th March 2016) - Wallace, Emma; Uijen, Maike J M; Clyne, Barbara; Zarabzadeh, Atieh; Keogh, Claire; Galvin, Rose; Smith, Susan M; Fahey, Tom
Abstract : Objectives: Following appropriate validation, clinical prediction rules (CPRs) should undergo impact analysis to evaluate their effect on patient care. The aim of this systematic review is to narratively review and critically appraise CPR impact analysis studies relevant to primary care. Setting: Primary care. Participants: Adults and children. Intervention: Studies that implemented the CPR compared to usual care were included. Study design: Randomised controlled trial (RCT), controlled before–after, and interrupted time series. Primary outcome: Physician behaviour and/or patient outcomes. Results: A total of 18 studies, incorporating 14 unique CPRs, were included. The main study design was RCT (n=13). Overall, 10 studies reported an improvement in primary outcome with CPR implementation. Of 6 musculoskeletal studies, 5 were effective in altering targeted physician behaviour in ordering imaging for patients presenting with ankle, knee and neck musculoskeletal injuries. Of 6 cardiovascular studies, 4 implemented cardiovascular risk scores, and 3 reported no impact on physician behaviour outcomes, such as prescribing and referral, or patient outcomes, such as reduction in serum lipid levels. 2 studies examined CPRs in decision-making for patients presenting with chest pain and reduced inappropriate admissions. Of 5 respiratory studies, 2 were effective in reducing antibiotic prescribing for sore throat following CPR implementation. Overall, study methodological quality was often unclear due to incomplete reporting. Conclusions: Despite increasing interest in developing and validating CPRs relevant to primary care, relatively few have gone through impact analysis. To date, research has focused on a small number of CPRs across few clinical domains only.